2015
DOI: 10.4314/bajopas.v7i2.24
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different feeding frequencies on growth performance and feed utilization of <i>Clarias gariepinus</i> (Burchell, 1822). Fingerlings

Abstract: The experiment was conducted to assess the growth performance and feed utilization of Clarias gariepinus under the feeding frequencies of T1 (twice/day), T2 (thrice/day), and T3 (four times/day) at 3% BWD per day over a period of 56 days. A total of 180 fingerlings with average weight of 2.39±0.19g and average length of 5.02±1.04cm were stocked at 15 fish per plastic container of 35 litres capacity. The highest weight gain recorded at the end of the experiment was 7.39±0.19g in (T3) and the lowest was 5.35±0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…Significant differences in all treatments of other parameters, (FCR, FCE, PER, PPV, EER, EPV, and LR) were found, the third treatment (T3) was the best of all treatments in this parameters and achieved better FCR than T2 and T1 while T2 was the better than T1 in parameters of feed utilization efficiency. The results cleared that the third treatment (T3) was the best of the feed utilization parameters, this results agree with Haruna et al (2014). They reported that, four feeding times gave the best result in terms of feed conversion ratio (FCR) and other growth indices.…”
Section: Effect Of Feeding Frequency On Feed Utilization Efficiency Osupporting
confidence: 86%
See 1 more Smart Citation
“…Significant differences in all treatments of other parameters, (FCR, FCE, PER, PPV, EER, EPV, and LR) were found, the third treatment (T3) was the best of all treatments in this parameters and achieved better FCR than T2 and T1 while T2 was the better than T1 in parameters of feed utilization efficiency. The results cleared that the third treatment (T3) was the best of the feed utilization parameters, this results agree with Haruna et al (2014). They reported that, four feeding times gave the best result in terms of feed conversion ratio (FCR) and other growth indices.…”
Section: Effect Of Feeding Frequency On Feed Utilization Efficiency Osupporting
confidence: 86%
“…However, the statistical analysis don't appear significantly differences between the second treatment and the first treatment, but the second treatment parameters (W2, g, TG, g, ADG, g, RGR, % and SGR/day, %) were higher than the first treatment parameters. These results cleared the positive effect of feeding frequency and increased feeding frequency resulted in greater growth for several fish species such as rainbow trout, Salmo gairdneri (Grayton and Beamish, 1977); Arctic charr, Salvelinus alpines (Jobling 1983), common carp, Cyprinus carpio (Charles et al, 1984); juvenile halibut, Hippoglossus hippoglossus L., (Schnaittacher et al, 2005) and goldfish, Carassius auratus (Priestly et al, 2006).These results in agreement with Daudpota et al (2016) reported that, the optimum feeding frequency of juvenile Nile tilapia (from initial body weight of 1.0 g to 5.8 g) is four times daily, Haruna et al (2014) reported that, four times per day feeding frequency had the best growth performance for the culture of Clarias gariepinus. Significantly (p<0.05) best growth was obtained in the 6 times a day treatment of Nile tilapia fingerlings (Pouomogne and Ombredane, 2001).…”
Section: Effect Of Feeding Frequency On Growth Performance Of Rabbitfsupporting
confidence: 66%
“…Results of this study ascertained that FF positively affected growth parameters and FCR of Asian sea bass fry, this complies with several studies evaluated the influence of FF on growth indicators of various fish species. According to Türker and Yildirim (2011) , increasing FF increased the SGR and FCR of trout fish, while Barakat et al (2011) found that increasing FF from three times/day led to increase SGR and achieved the best FCR of Siganus rivulatus , Haruna et al (2014) mentioned that the highest SGR and the best FCR of Clarias gariepinus achieved with increasing of FF, Choudhury et al (2002) decided SGR and FCR of Labeo rohita were the best with increasing of FF. Moreover, Pouomogne and Ombredane (2001) noticed SGR and FCR of tilapia were improved and associated with increasing of FF.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of feeding frequency on growth has been studied intensively in various fish species. Previous research has shown on tilapia, Oreochromis niloticus (Jegede & Olorunfemi, 2013), Oreochromis mosambicus (Luthada & Jerling, 2013), Clarias gariepinus (Haruna et al, 2014;Jamabo et al, 2015), Carassius auratus (Habib et al, 2014), that the feeding frequency three to four times a day led to an increase in growth. Still, Acipenser stellatus (Dicu et al, 2013), O. niloticus (Bin et al, 2014;Kaya & Bilguven, 2015;Alal, 2018), Sebates inermis (Oh et al, 2018), C. auratus (Hafeez-ur-Rahman et al, 2015) and Epinephelus coiodes (Amadou et al, 2019) achieved optimal growth on a feeding frequency twice a day.…”
Section: Introductionmentioning
confidence: 94%